The Detection of an Extremely Bright Fast Radio Burst in a Phased Array Feed Survey - Bannister, K.; Shannon, Ryan; Macquart, Jean-Pierre; Flynn, C.; Edwards, P.; O'Neill, M.; Oslowski, S.; Bailes, M.; Zackay, B.; Clarke, N.; D'Addario, L.; Dodson, R.; et al. (Institute of Physics Publishing, 2017)
We report the detection of an ultra-bright fast radio burst FRB)from a modest, 3.4-day pilot survey with the Australian Square Kilometre Array Pathfinder. The survey was conducted in a wide- field fly’s-eye configuration using the phased-array-feed technology deployed on the array to instantaneously observe an effective area of 160 deg2, and achieve an exposure totalling 13200 deg2 hr. We constrain the position of FRB 170107 to a region 8 ́ x 8 ́ in size(90% containment)and its fluence to be 58 ± 6 Jy ms. The spectrum of the burst shows a sharp cutoff above 1400 MHz, which could be due to either scintillation or an intrinsic feature of the burst. This confirms the existence of an ultra-bright (> 20 Jy ms) population of FRBs.